"Freedom to move through the house": How a healthy housing initiative improves quality of life in Aotearoa New Zealand - Elinor Chisholm; Amber Logan; Clare Aspinall; Cheryl Davies; Philippa Howden-Chapman; Ellie Johnson; Nevil Pierse (Elsevier, 2024)
Objective: This study explores experiences of the Healthy Housing Initiative (HHI). Aimed at children at risk of housing-related illness, the HHI package includes the provision of items such as curtains, heaters, bedding, and insulation, advocacy to encourage landlords to install improvements, and education and advice to help people optimise their home environment. Methods: We conducted semi-structured, in-depth interviews with 20 people living in rental housing who received the HHI intervention. Results: Participants felt heard and supported by HHI assessors. They reported that the intervention increased the warmth and dryness of the home, improved their respiratory and mental health, reduced their bills, and enabled the use of more parts of their home. However, some continued to live in cold and damp conditions due to structural inadequacies and energy poverty. Conclusions: The qualitative evidence presented in this study shows how health-focussed interventions also benefit quality of life. Implications for public health: This research emphasises that healthy housing interventions can yield extensive benefits by adopting a holistic and home-based approach. Such interventions have the potential to create improvements in individuals' lives far beyond health.